Teacher telling in the mathematics classroom: A microlevel study of the dynamics between general and contextualized knowledge - Chesnais, Aurelie; Horoks, Julie; Robert, Aline; Rogalski, Janine (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2022)
In this article, we analyze moments of teacher telling (MTT) involving the exposition of new knowledge to students. We first specify the theoretical framework used for our analyses and describe our global methodology, focusing on teacher telling moments as taking part in the students’ mathematics learning. Then, we review the literature on this topic and develop a specific tool, called a “proximity,” to study MMTs in relation to whole-class scaffolding. Finally, we compare two high school teachers’ practices in teaching the same content — variation of functions for 10th grade students — to illustrate this new analytical lens. In the conclusion, we discuss our approach and develop several research perspectives.